1970
DOI: 10.3329/bvet.v27i2.7554
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of goat semen in Tris-Citrate-Glucose extender containing glutathione

Abstract: Glutathione (GSH) 0 (control), 2, 4 and 8 mM was used in the preservation of chilled goat semen. Treated and control samples were kept at 4 -5°C up to seven days. Sperm motility and acrosome abnormality were assessed daily under phase contrast microscope. The sperm motility was significantly (P<0.01) higher in the semen treated with 8 mM GSH. Optimum sperm motility (≥50%) for artificial insemination was retained for three days with 2 and 4 mM GSH and up to four days with 8 mM GSH. Acrosomal damage was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
2
7
2
1
Order By: Relevance
“…Attributes of semen especially ejaculate volume with good concentration, and motility of spermatozoa is important to create opportunity of producing maximum number of AI doses from an ejaculate. The volume of ejaculate was reported low and was varied between Black Bengal bucks, 2‐4 which were in agreement with the current investigation. The concentrations of spermatozoa in black Bengal bucks reported by other authors 3,29,30 were similar with the current estimation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Attributes of semen especially ejaculate volume with good concentration, and motility of spermatozoa is important to create opportunity of producing maximum number of AI doses from an ejaculate. The volume of ejaculate was reported low and was varied between Black Bengal bucks, 2‐4 which were in agreement with the current investigation. The concentrations of spermatozoa in black Bengal bucks reported by other authors 3,29,30 were similar with the current estimation.…”
Section: Discussionsupporting
confidence: 92%
“…The concentrations of spermatozoa in black Bengal bucks reported by other authors 3,29,30 were similar with the current estimation. However, Rajuana et al 31 reported higher concentration of spermatozoa, while Mishra et al 4 reported very low concentration of spermatozoa in Black Bengal bucks compared to the current investigation. The variation could be due to the differences in environment and the differences of techniques and semen collectors 32,33 .…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations